The influence of positive work attitude and emotion on intention to leave among ICT professionals in Malaysia / Safiah Omar - Omar, Safiah (2015)
The disequilibrium growth between the skills supplies and the growth of technologies raise a concern for this study to carry out research in the area of intention to leave among the ICT Professionals in Malaysia. This is due to the statistics report on the high rate of turnover in the ICT industry. At the same time the role of the ICT industry is also very important in contributing to the growth of the country. Two types of intention to leave were tested in this study which is the intention to leave the organization and the intention to leave the career. A considerable amount of literature has been published on intention to leave but mostly studied from the negative perspectives such as job dissatisfaction, burnout, work conflicts, psychological distress, and employee disengagement. This study answering the call from the positive psychology movement where the study area focus on positive side and the strengths of individual such as positive work attitude and work emotion in determining the factors to reduce the levels of intention to leave. The constructs are career commitment, positive organizational behaviour (POB), work happiness as mediator, and career adaptability as moderator. Using questionnaires as the main assessment instruments, this study adopts quantitative approach for the analyses and using mainly on structural equation modelling (SEM). Confirmatory factor analyses (CFA) were conducted among all the constructs prior to the hypothesized testing. Results from the CFA suggested that the hypothesized framework needed to be separated between intention to leave the organization and intention to leave the career. The two hypothesized framework were tested using SEM and good model fit indices were achieved for both framework. Both Framework 1 (intention to leave the organization) and Framework 2 (intention to leave the career) found that POB was negatively related to intention to leave and positively related to work happiness, while work happiness was negatively related to intention to leave. Career commitment was found to be negatively related to intention to leave but not to work happiness. Work happiness also partially mediates the relationships between positive organizational behaviour and intention to leave for both frameworks. The analyses also showed that career control and career curiosity in the constructs of career adaptability moderate the relationships between work happiness and intention to leave both in Framework 1 and Framework 2. The findings indicated that the encouragement of positive attitudes such as hope, optimism, resilience, the commitment that individuals have over their career, and the emphasis on positive emotions such as work happiness can contribute to reduce the level of intention to leave. The existence of career adaptability did not increase the level of intention to leave when work happiness exist which means organization may encourage and provide adaptability trainings to increase the career adaptability level among the ICT professionals. The research findings are discussed in relation to the literature. Implications and recommendations for the future research are also presented.